Effects of prior exercise on the performance of intense isometric exercise. Issue 1 (March 1988) - Maughan, R J
Abstract : The influence of a regimen designed to lower the muscle glycogen content on the capacity to perform a single brief isometric contraction has been studied. Eight male subjects performed a single exhausting isometric contraction of the knee extensor muscles at a tension corresponding to 60% of maximum voluntary contraction (MVC). This was followed by prolonged cycling exercise at a work rate equivalent to approximately 75% of maximum oxygen uptake in order to reduce the muscle glycogen content. A diet low in carbohydrate was consumed for the remainder of this day in order to retard the resynthesis of muscle glycogen. The isometric contraction at 60% of MVC was repeated on the following day. Endurance time on the first day was 53.8 +/- 8.4 s (mean +/- SD); this was reduced (45.8 +/- 12.1 s; p less than 0.02) on the second day. From previously published data on rates of muscle glycogen utilisation during isometric exercise, it seems probable that insufficient glycogen is available in the muscle under the low carbohydrate condition to enable maximum performance to be achieved.